The Effectiveness of Problem-Based Learning in Enhancing Students’ Conceptual Understanding and Learning Outcomes in Islamic Religious Education - Muhammad Riyadh; Budi Pangastuti; Endah Permanasari; Hana Fauziah; Siti Roudhotul Jannah (CV. Creative Tugu Pena, 2025)
This study aims to analyze the effectiveness of the Problem-Based Learning (PBL) model in improving students’ conceptual understanding and learning outcomes in Islamic Religious Education (PAI). Using a systematic literature review approach, this research examines findings from empirical studies published between 2019 and 2024 sourced from Google Scholar, DOAJ, and nationally indexed journals. The review reveals that PBL significantly enhances students’ understanding of Islamic concepts by engaging them in authentic, contextual problems that require analytical thinking, argumentation, and reflective inquiry. Students demonstrate deeper comprehension when exposed to real-life cases related to Islamic teachings, enabling them to interpret and apply religious concepts within practical contexts. The model also contributes to improved cognitive achievement, as evidenced by increased post-test scores and strengthened higher-order thinking skills. Furthermore, PBL fosters students’ motivation and engagement through collaborative group activities, meaningful discussions, and student-centered learning dynamics. Several supporting factors such as authentic problem design, teacher facilitation, structured group work, and reflective practice are identified as essential elements in ensuring the successful implementation of PBL. Overall, this study concludes that PBL is an effective pedagogical model for advancing both conceptual understanding and learning outcomes in PAI, making it suitable for 21st-century Islamic education demands.